Photoelectrocatalytic Degradation of Organic Compound Congo Red Using TiO2/Ti Electrode - Muh. Edihar; Kurnia Sri Yunita; Kaharuddin Kaharuddin (LPPM ISTEK 'Aisyiyah Kendari, 2023)
Abstract: In this study, we synthesized photobilized TiO2 on a Ti plate and tested its photoelectrocatalytic activity towards Congo Red. The background of this research is to develop an effective and environmentally friendly water treatment method. The main method used was the sol-gel synthesis of TiO2 prepared from titanium tetra isopropoxide as a complexing agent, followed by photobilization on a Ti plate. Material characterization was conducted using XRD technique, portable Potentiostat (e-DAQ), and UV-Vis DRS (Diffuse Reflectance Spectrophotometric) spectroscopy. The results of this research showed that the TiO2 synthesis produced Anatase crystal structure with particle size of 13–16 nm and a band gap of 3.20 eV. Furthermore, the photoelectrocatalysis test demonstrated that TiO2/Ti exhibited activity in degrading Congo Red. The main conclusion of this study is that the synthesis of TiO2/Ti using the Sol-Gel method and immobilization on a Ti plate can enhance the photodegradation efficiency towards Congo Red. This finding has significant implications in the development of more effective and environmentally friendly water treatment technologies.